After Ofsted failure: the emotional journeys of head teachers - Heery, Paul (2018)
This thesis presents four case studies of Head Teachers whose schools received the lowest Ofsted inspection rating of 4 – Inadequate. It examines the impact of the judgement on the individual Head Teachers, both on their career and also on their emotional lives. It considers the role of Ofsted inspection within an era of increasing accountability, and looks at the extent to which these four individuals were able to lead their schools from this failure to a more successful and stable situation, and the emotional journeys that accompanied this process. The case studies are based on a series of semi-structured interviews with the four Head Teachers over a period of two to three years after the initial inspection. Other key sources of evidence are considered, including Ofsted reports, school achievement data, and interviews with other stakeholders. The study concludes that long-term success for the school and the school leader depends upon the Head Teacher successfully managing the key stages in this emotional journey, from surviving the initial emotional crisis, through a period of emotional labour, to emotional regulation, before achieving emotionally healthy leadership. The successful navigation of this process by some of the Head Teachers enabled them to focus on key leadership practices resulting in long-term improvement. Where this journey was not successfully managed, the impact on long-term success and career advancement was considerable. Hundreds of schools each year are graded inadequate by Ofsted, with a larger number judged to be requiring improvement. The outcomes of this research have potential implications for the way that Head Teachers can be supported to improve their schools following this failure, whilst at the same time safeguarding their own emotional health and wellbeing.